CONSUMER BEHAVIOUR AND ITS IMPACT ON STARTUP BRAND LOYALTY:A SURVEY-BASED STUDY - Sahu, Sagar; Kshatriya, Sunita; Jha, S.N. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of this study is to examine the influence of consumer behaviour on brand loyalty among entrepreneurs in India, with a particular emphasis on the consumer base in Chhattisgarh. The objective of the research is to comprehend the impact of demographic variables, including age, gender, education level, and income, on brand loyalty, as well as product quality, pricing, and customer service. The study determined that brand loyalty is substantially influenced by product quality, age, and education level, while pricing, customer service, gender, and income do not have a substantial impact, based on data collected from 214 respondents using ordinal regression analysis. The findings indicate that businesses should prioritise the improvement of product quality and the customisation of marketing strategies to target specific age and education demographics in order to cultivate brand loyalty. The results offer entrepreneurs valuable insights to refine their consumer engagement strategies and align their offerings with customer preferences.